Graphene oxide membrane used in water purification device - Zhu, Wenqi (2015)
Nowadays, approximately half of the population worldwide locating in over 88 nations is experiencing severe water scarcity. Moreover, considering the fast population boom, alterations in people‟s living style, more economic events, and pollution that damage clean water resources, it is expected that the proportion of global population that experience water scarcity rise to 60% by 2025. The utilization of dirty water results in 80 to 90% among all diseases as well as over 1/3 of deaths in developing economies [1]. Along with the rapidly ascending awareness on water resource, water treatment and purification has been taken seriously and studied by scholars. In these researches, with its atomic thickness and accurate sieving performances, graphene base materials present great promise as a film of ultra-high permeability for water purification and treatment. However, a significant gap exists in the literature between real graphene base material purification and degerming devices. This study is to build a graphene oxide model through COMSOL and water desalination and treatment process is simulated, time consumed and permeability over this process is investigated. By comparing the volumetric flow rate and percentage of effective area, the suitable pore size and porosity was obtained. Further experience is taken to find a proper preparation method of graphene oxide and effect of purification. Lastly, the process and its filter cartridges of home used water purification device is sugguested.